2012
DOI: 10.5754/hge12566
|View full text |Cite
|
Sign up to set email alerts
|

Effective Weight Control and Normalization of Metabolic Parameters after Laparoscopic Sleeve Gastrectomy: A Single Center Experience

Abstract: Results of this study demonstrate that LSG induces stable weight loss and resolution of obesity-associated comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A recent study demonstrated that LSG induces stable weight loss and resolution of obesity-associated comorbidities [31]. Our study is the first to assess the association of the rs9939609 FTO gene polymorphism and weight loss after LSG.…”
Section: Resultsmentioning
confidence: 95%
“…A recent study demonstrated that LSG induces stable weight loss and resolution of obesity-associated comorbidities [31]. Our study is the first to assess the association of the rs9939609 FTO gene polymorphism and weight loss after LSG.…”
Section: Resultsmentioning
confidence: 95%
“…LSG has become increasingly popular around the world since 2000 [ 35 ]. LSG has been an effective, stand-alone therapy for morbidly obesity, with stable weight loss and resolution of obesity-associated comorbidities [ 36 , 37 ], but there have been few studies of the association between genetic factors and the outcomes of LSG. In 2016, Shanti et al.…”
Section: Personalized Obesity Treatment By Bariatric Surgerymentioning
confidence: 99%
“…LSG is a recently introduced restrictivetype bariatric procedure and is currently the most common surgical option employed in obesity management. Indeed, this technique has a good weight-loss efficacy and has been widely demonstrated to improve obesity related-comorbidities including type 2 diabetes, dyslipidemia, hypertension and many others [37][38][39]. However, the exact pathophysiological mechanisms behind its beneficial effects, beyond the mere weight reduction, are not completely understood.…”
Section: Endocrine Researchmentioning
confidence: 99%